The Effect of Coloring Activities on the Fine Motor Skills of Early Age Children 5 – 6 Years in the Pembina State Kindergarten, Pancur Batu District - Sri Wahyuni; Kamtini (Indonesian Journal of Advanced Research, 2023)
The aim of this research is to find out how coloring activities impact the fine motor skills of children aged 5-6 years at the Pembina State Kindergarten, Pancur Batu District. This research uses an experimental type of research. This research design uses True Experimental Design, with a post-test only control group design. The experimental and control groups consisted of each other. This research involved 30 early childhood children aged between 5 and 6 years. The independent variable in this research is coloring activities and the dependent variable is fine motor development. The data collection method consists of structured observation and analysis data collected using the t-test with a significance level of α = 0.05. The results of the research show that there is a significant influence of coloring activities on the fine motor development of young children in the Pembina State Kindergarten, Pancur Batu District. This is proven by statistical calculations through the average value given different treatments, namely 13.13 for the experimental class and 7.66 for the control class. Where the t-test results show a tcount of 12.128. For hypothesis testing criteria using a real level of 0.05 with dk = n1 + n2-2 or dk 28, the ttable is 1.701. So it can be concluded that tcount 12.128 > ttable 1.701, which means Ha is accepted and H0 is rejected or the same as coloring activities have a significant effect on the fine motor development of early childhood children 5-6 years old in the Pembina State Kindergarten, Pancur Batu District.